Kachtitsis ou le désenchantement du dépaysement - Gunnar De Boel (Cahiers Balkaniques)
The author Nikos Kachtitsis is an interesting exponent of Greek emigration after the second World War because of the multiple aspects, well documented in his correspondence, of his motivation to emigrate to Montréal. Reality soon clashed with his dreams, as he realized that it was not all roses in Canada either. After ten years, he dreamed of London and Paris, forgetting he had shouted out his hate for the French before and had found London architecture dismal. It comes therefore as no surprise that in the end he feels at home neither in Greece nor abroad, and that he thinks the best solution is to stay where you are, like his friends had done, to allow your dreams to remain intact. For Kachtitsis, his real fatherland are his dreams, along with his memories and above all the friends who share them. Dreams are that something which will always consume our souls, in spite of all setbacks. Finding that something is for Kachtitsis the task of literature.